2018
DOI: 10.35814/jifi.v16i1.434
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Potential of Ethanol Extract of Sonchus Arvensis L. Leaves on Isoproterenol-Induced Myocardial Infarction in Rat

Abstract: Sonchus arvensis L. leaves have been used traditionally to treat various disease conditions. This study is designed to evaluate cardioprotective potential of ethanol extract of S. arvensis leaves on isoproterenol-induced myocardial infarction in Wistar rat. Male Wistar albino rats were divided into three main groups: negative control (saline only), positive control (isoproterenol only), and S. arvensis extract treated groups. S. arvensis extract was administered in three doses; 50, 100, and 200 mg/kg b.w. p.o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In our previous study, pretreatment with ethanolic extract of S. arvensis (50, 100 and 200 mg/kg bw) daily for a period of 14 days attenuated significantly the serum activities of AST, ALT, CK, CK-MB and LDH enzymes compared to ISO alone treated (positive control) rats [12]. However, increase of the dose did not increase its activities.…”
Section: Effect Of Fractions Of Sonchus Arvensis Ethanolic Extract Onmentioning
confidence: 80%
“…In our previous study, pretreatment with ethanolic extract of S. arvensis (50, 100 and 200 mg/kg bw) daily for a period of 14 days attenuated significantly the serum activities of AST, ALT, CK, CK-MB and LDH enzymes compared to ISO alone treated (positive control) rats [12]. However, increase of the dose did not increase its activities.…”
Section: Effect Of Fractions Of Sonchus Arvensis Ethanolic Extract Onmentioning
confidence: 80%
“…As well as being a potential ACE inhibitor, [35] reported that tempuyung has cardioprotective properties that protect the heart considering hypertension is a cardiovascular disease. Tempuyung leaves are also known to have effectiveness as a diuretic, anti-inflammatory and antipyretic, and contain flavonoids in the form of luteolin [36], and contains kaempferol, orientin, and quercetin [27].…”
Section: Inhibition Of Tempuyung Extract and Fraction To Acementioning
confidence: 99%